Transnational Communication as Deliberation, Ritual, and Strategy - Brüggemann, Michael; Wessler, Hartmut (Communication Theory, 2014)
Globalized communication flows transcend and transform national borders. Transnational media outlets targeting audiences around the globe, issues of global concern are subjected to border-crossing public debates, media events receive transnational attention, and public diplomacy efforts succeed—and fail—in characteristic patterns around the world. In response to these phenomena the article shows how the study of transnational communication can benefit from combining 3 theoretical perspectives that are rarely studied together: communication as deliberation, as ritual, and as strategy. Particularly in explaining the failures of transnational communication, explanatory potential often seems to lie just outside the limited vision of each of the 3 perspectives—and outside the scope of empirical analyses that are limited to Western contexts.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Europe (lieu de production du savoir); _Nettoyé